2003
DOI: 10.1002/bdra.10114
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial cleft malformations: Associations with maternal and infant characteristics in Washington State

Abstract: The prevalences of orofacial clefts in Washington State in 1987-90 were similar to those of other states. This study is among the first to report a greater relative risk for isolated CL +/- CP among the infants of mothers < 20 years compared to older mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
39
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 32 publications
10
39
1
2
Order By: Relevance
“…However, larger studies failed to identify advanced maternal age as a risk factor for OCs [31,32]. Conversely, other studies found a greater risk for CL among younger mothers [33,34]. Infant sex influences the risk for OCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, larger studies failed to identify advanced maternal age as a risk factor for OCs [31,32]. Conversely, other studies found a greater risk for CL among younger mothers [33,34]. Infant sex influences the risk for OCs.…”
Section: Discussionmentioning
confidence: 99%
“…CHARS data have been used in many different epidemiologic studies to evaluate a range of birth defects. [17][18][19][20] Women were eligible for this study if they gave birth to two singleton infants between 1998 and 2008. Women whose first or second birth involved a multiple birth were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to that review, this one has included 20 additional studies 6,7,8,9,10,11,12,13,14,24,43,79,83,95,99,102,103,122,125,188 that have added about 10,000 cases of defects, and 800,000 of controls. Another difference between the two reviews is that 19 studies about abdominal wall defects were included in the meta-analysis of the gastro-intestinal system in the previous review, whereas these defects were classified as pertaining to the musculoskeletal system in this review.…”
Section: Discussionmentioning
confidence: 99%
“…While this investigation was being carried out, a systematic review with 101 observational studies was published, and showed an association between maternal smoking during pregnancy and different birth defects in children 5 . This review, however, did not include a considerable number of relevant studies 6,7,8,9,10,11,12,13,14 . Moreover, defects of the abdominal wall, such as congenital diaphragmatic and inguinal hernia, gastroschisis, and omphalocele, which should be considered musculoskeletal abnormalities, according to the 10 th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) 15 were classified as gastrointestinal defects.…”
Section: Introductionmentioning
confidence: 99%